2011
DOI: 10.1007/s10029-011-0809-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the use of fibrin sealant in abdominal-wall repair surgery

Abstract: Compared with mechanical methods, fibrin sealant is an efficacious alternative for mesh fixation postsurgery of the abdominal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
14
0
3
Order By: Relevance
“…Additionally, the same holds true for our secondary measures as hernia recurrence rate, as longer follow-up of the patients may reveal additional surgical site occurrences. Also, the amount of fibrin sealant used in our study (2 ml per 10 cm 2 defect size), although within the maximum range suggested by the manufacturer, is a greater amount than previous studies (1-2 ml per 16-40 cm 2 ) that have demonstrated successes with its use [17,18]. A lesser amount of fibrin sealant may prove advantageous and further studies are ongoing to explore this topic.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Additionally, the same holds true for our secondary measures as hernia recurrence rate, as longer follow-up of the patients may reveal additional surgical site occurrences. Also, the amount of fibrin sealant used in our study (2 ml per 10 cm 2 defect size), although within the maximum range suggested by the manufacturer, is a greater amount than previous studies (1-2 ml per 16-40 cm 2 ) that have demonstrated successes with its use [17,18]. A lesser amount of fibrin sealant may prove advantageous and further studies are ongoing to explore this topic.…”
Section: Discussionmentioning
confidence: 59%
“…Tissucol Ò was used in the space between the prosthesis and the hernia sac, at an average of 1 ml per 16 cm 2 of defect size [18]. A significant reduction in the incidence and volume of the seromas in the sealant group was noted at 7 days and 1 month after surgery [18]. Similarly, Férnandez et al noted significantly less local morbidity and a shorter hospital stay in patients who had Tissucol applied following incisional hernia repair with dermolipectomy [19].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Generally, sutures are generally used to secure the prosthetic mesh; however, that may lead to chronic pain and other problems such as numbness or groin discomfort, presumably through tension or nerve compression [5]. Some studies showed that chronic pain was influenced by the type of the mesh implanted and its fixation [22,23]. For these reasons, some surgeons searched for a new type of atraumatic methods of fixation.…”
Section: Discussionmentioning
confidence: 99%